(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Vinegar is a product of double fermentation including the primary stage by anaerobic conversion of fermentable sugars to ethanol by Saccharomyces species, and the second one is the oxidation of ethanol to acetic acid by means of micro-organisms, commonly used by Acetobacter aceti. The Feronia limoniavariety of wood appleswas cut with a knife, crushed with a mixer to make them juicy, sampled, and immediately frozen followed by pre-treatment and depectinization). The excellent result was acquired at 0.0004 % (w/v) of wood apple. At 48 hrs., 10% yeast cellular concentration produced 7.6% of alcohol. Alcohol manufacturing steadily reduced sugar concentration from around13% to 11%.After fermentation, the vinegar produced a colorof pale brownish. The results confirmed that acetic acid concentrations extended with an increase in the inoculum degree tested. The best acetic acid concentrations of 5.32 % and 5.11 % were discovered on the five and 10 % inoculum stages, respectively for the very best alcohol-contained pattern (SET C). The numerous parameters assessed evaluate favorably with the usual magnitudes.